The hooligans - Deutermann, P. T., (Peter T.), 1941- (St. Martin's Press, 2020)
"A gripping and authentic World War II naval adventure by a master storyteller. The Hooligans fictionalizes the little-known but remarkable exploits of "The Hooligan Navy" that fought in the Pacific theatre of World War II. Loosely-organized in fast moving squadrons, PT (patrol torpedo) boats were the pesky nemesis of the formidable Japanese navy, dubbed "the mosquito fleet" and "devil boats" for their daring raids against warships, tankers, and transport ships. After the Pearl Harbor raid plunges America into war, young surgical resident Lincoln Anderson enlists in the Navy medical corps. His first deployment comes in August 1942 at Guadalcanal, when after a brutal sea battle and the landing of Marines on the island, Anderson finds himself triaging hundreds of casualties under relentless Japanese air and land attacks. But with the navy short of doctors, soon Anderson is transferred to serve aboard a PT boat. From Guadalcanal to the Solomon Islands to the climactic, tide-turning battle of Leyte Gulf, Anderson and the crew members of his boat confront submarines and surface ships, are attacked from air by the dreaded Kawanishi flying boats, and hunted by destroyers. In the end, Anderson must lead a division of boats in a seemingly-impossible mission against a Japanese battleship formation-and learn the true nature of his character. Informed by P. T. Deutermann's own experience as a commander of a patrol gunboat in Vietnam, The Hooligans is first-rate military adventure fiction"--